A home‐built digital optical MRI console using high‐speed serial links. Issue 2 (8th August 2014) - Tang, Weinan; Wang, Weimin; Liu, Wentao; Ma, Yajun; Tang, Xin; Xiao, Liang; Gao, Jia‐Hong
<x xml:space="preserve">Abstract</x> Purpose To develop a high performance, cost‐effective digital optical console for scalable multichannel MRI. Methods The console system was implemented with flexibility and efficiency based on a modular architecture with distributed pulse sequencers. High‐speed serial links were optimally utilized to interconnect the system, providing fast digital communication with a multi‐gigabit data rate. The conventional analog radio frequency (RF) chain was replaced with a digital RF manipulation. The acquisition electronics were designed in close proximity to RF coils and preamplifiers, using a digital optical link to transmit the MR signal. Results A prototype of the console was constructed with a broad frequency range from direct current to 100 MHz. A temporal resolution of 1 μs was achieved for both the RF and gradient operations. The MR signal was digitized in the scanner room with an overall dynamic range between 16 and 24 bits and was transmitted to a master controller over a duplex optic fiber with a high data rate of 3.125 gigabits per second. High‐quality phantom and human images were obtained using the prototype on both 0.36T and 1.5T clinical MRI scanners. Conclusion A homemade digital optical MRI console with high‐speed serial interconnection has been developed to better serve imaging research and clinical applications. Magn Reson Med 74:578–588, 2015. © 2014 Wiley Periodicals, Inc.